Comparative Assessment of the Analgesic Efficacy of Tramadol and Diclofenac Sodium Rectal Suppository in Subjects Undergoing Laproscopic Tubal Ligation - Baranda, Ushma K; Baranda, Sheetal K; Chaudhary, Mikita (Academia Anesthesiologica International, 2019)
Background: Several drugs such as NSAID s or opiods can be used orally, intravenously or intramuscularly for treatment of post operative pain. The aim of our study was to compare the analgesic efficacy of tramadol and diclofenac sodium suppository and the secondary aim was to monitor and treat the complications if any. Subjects and Methods: Fifty female patients of ASA I and II in the age group of 24-42 posted for laproscopic tubal ligation were enrolled in the study. Verbal analogue scale (0- no pain to 10- worst possible pain) score reading was explained. In the pre operative room all the patients were randomly allocated in two groups by a computer generated list. Post operatively all the hemodynamic parameters and VAS score were recorded at regular intervals of 1, 2, 4, 6, 8, 10,12hrs. Pain was assessed by a staff trained to VAS score assessment and was blinded to the study group. Side effects of nausea and vomiting were noted. Results: Group 2 had high mean age of the study participants compared to group 1 but the comparison was non-significant.(p?0.05) Only one patient in group A (tramadol) complained of nausea and vomiting. In group A 69% patients needed 1 rescue analgesic at 8 hrs, 11% at 6hrs, 9% at 4hrs and 11% at 10 hrs whereas in group B 64.1% patients needed 1 rescue analgesic at 8hrs, 16.2% at 10 hrs and 19.7 % at12 hrs. Conclusion: From above findings it was concluded that analgesic efficacy of tramadol and diclofenac sodium suppository is comparable. Rectal administration of tramadol reduces the incidence of nausea and vomiting.